Molecularly imprinted ormosil as a sorbent for targeted dispersive solid phase micro extraction of pyriproxyfen from strawberry samples. (April 2023) - Hayat, Muhammad; Manzoor, Suryyia; Raza, Hina; Khan, Muhammad Imran; Shanableh, Abdallah; Sajid, Muhammad; Almutairi, Tahani Mazyad; Luque, Rafael
Abstract: Novel molecularly imprinted organically modified silica was prepared by reacting acrylamide and 3-(tri-methoxysilyl) propyl methacrylate followed by condensation and hydrolysis with tetraethyl ortho -silicate for the determination of pyriproxyfen. The sorbent proved to be highly selective for the template molecule, pyriproxyfen. The characterization of sorbent was carried out using SEM, BET and TGA. The prominent peaks in FTIR at 3700 cm −1 and 1071 cm −1 confirmed the stretching of amide group's N –H and Si–O–Si bond linkage of MIOrmosil . The pseudo-first-order model (R 2 0.99) described the adsorption kinetics of the MIOrmosil, whereas among adsorption isotherms, Freundlich model showed the best fit (R 2 0.99). The molecularly imprinted silica was applied for the determination of target analytes from strawberries sample using dispersive solid-phase micro extraction (DSPME) followed by high-performance liquid chromatography (HPLC). The LOD (4.93 x10 −5  μg mL −1) and LOQ (1.49 x10 −4 μg m- 1 ) values were calculated by signal to noise ratio through HPLC. Results show that the maximum binding capacity and percentage recovery values of MIOrmosil were 13 mg g −1 (n = 5) and 97.3% respectively. Graphical abstract: Image 1 Highlights: A novel molecularly imprinted ormosil (MIormosil ) was synthesized by radical polymerization followed by sol-gel method using pyriproxyfen as template. MIormosil was applied as a sorbent for the targeted DSPME of pyriproxyfen from strawberry samples. MIormosil showed excellent selectivity for the target analyte.